Rabeprazole suppressed gastric intestinal metaplasia through activation of GPX4-mediated ferroptosis - Xie, Jing; Liang, Xinhua; Xie, Fangfang; Huang, Canxin; Lin, Zijun; Xie, Shuping; Yang, Fangying; Zheng, Fengfeng; Geng, Lanlan; Xu, Wanfu; Gong, Sitang; Xiang, Li (Frontiers in Pharmacology, 2024)
Background. Gastric intestinal metaplasia is a common pathological feature in patients with Helicobacter pylori (H. pylori) infection. Rabeprazole was widely used as the first-line regimen for H. pylori infectious treatment. The objective of this study is to explore the mechanism of rabeprazole in gastric intestinal metaplasia treatment. Methods. Real-time PCR, western blotting (WB) and ROS analysis were conducted to confirm that rabeprazole could alleviate ferroptosis to suppress gastric intestinal metaplasia. cellular fraction, luciferase and chromatin immunoprecipitation (ChIP) were used to identify the mechanism underlying rabeprazole modulated ferroptosis. Results. Herein, we found rabeprazole treatment led to inhibit CDX2 and MUC2 expression, alleviating gastric intestinal metaplasia, which was attributed to enhanced ferroptosis characterized by decreased GPX4 expression. Inhibition of ferroptosis by ferrostatin-1 (Fer-1) could reverse decreased CDX2 and MUC2 expression caused by rabeprazole. Mechanically, Rabeprazole could inhibit CREB phosphorylation and nuclear translocation, which further decreased the binding of CREB to GPX4 promoter, reducing GPX4 transactivity. Moreover, endogenous PKA interacted with CREB, and this interaction was drastically destroyed in response to rabeprazole treatment. Most importantly, enhanced ferroptosis was observed in H. pylori-infected gastric intestinal metaplasia in comparison to HC control. Conclusion. These findings suggested that rabeprazole induced ferroptosis to reduce CDX2 expression in gastric epithelial cells through PKA/CREB cascade signaling, implying that targeting ferroptosis could be a promising strategy in improving gastric intestinal metaplasia during H. pylori-infected patients.